حوار أصول التفسير وقواعده: قراءة في المنجز، وآفاق التطوير مع د. محمد صالح سليمان - سليمان، محمد صالح محمد; عكراش، يوسف (مركز نماء للبحوث والدراسات, 2023)
يأتي هذا الحوار الذي أجراه يوسف عكراش مع محمد صالح سليمان بغية تسليط الضوء على أحد أبرز موضوعات الدرس التفسيري التي أثير النقاش حولها قديمًا وحديثا، ألا وهي أصوله وقواعده أملين رصد المنجز واستشراف الآفاق من خلال مناقشة قضايا عدة من أبرزها: مداخل الضبط المفهومي وإشكالاته، والغاية من أصول التفسير، مع الوقوف على مدى اشتمال مقدمات وكتب التفاسير على أصول التفسير وقواعده، وإمكانية استخلاصها من لدن المتخصصين، ثم مناقشة المسار النظري المجرد لأصول التفسير، ومدى الحكم بقاعدة القواعد في الإنتاج العلمي المعاصر...، ليختتم القول في الحوار بالتطرق لمسألة ترسيم تسمية علم أصول التفسير وعلم قواعد التفسير على نحو منهجي منضبط يستوعب سياجه المعرفي الشقين النظري والتطبيقي. This interview aims to shed light on one of the most prominent topics of the interpretive lesson that has been discussed in the past and the present, namely its principles and rules, with the hope of monitoring what has been achieved and anticipating the horizons through discussing several issues, the most prominent of which are: The approaches to conceptual control and its problems, and the purpose of the principles of interpretation, while determining the extent to which the introductions and books of Al-Tafaseer (interpretations) include the principles and rules of interpretation and the possibility of extracting them from specialists. Then, discuss the abstract theoretical path of ‘the principles of interpretation’, and the extent of the rule of ‘basics in contemporary scientific production...’, to conclude the dialogue by addressing the issue of demarcating the name of the science of the ‘Principles of Interpretation’ and the science of the rules of interpretation in a disciplined and systematic manner whose cognitive framework includes both the theoretical and applied aspects.
Keywords: الإنتاج العلمي المعاصر -- علم أصول التفسير -- قضايا التفسير